Application of biomaterials in mesenchymal stem cell based endometrial reconstruction: current status and challenges - He, Ling; Li, Qianrong (Frontiers in Bioengineering and Biotechnology, 2025)
Severe endometrial injuries may cause thin endometrium and intrauterine adhesion in women which can result in uterine factor infertility. Current treatments, including surgical separation of adhesions and hormonal regeneration of the endometrium, often fail to prevent re-adhesion and achieve satisfactory reproductive results. Recently, mesenchymal stem cells (MSCs) have become a promising new treatment for IUA. However, challenges such as cell survival and transplantation limit the effectiveness of MSC therapy. Researchers have explored various approaches to enhance the therapeutic efficiency of MSCs. Among these, biomaterials have been frequently employed due to their biocompatibility, degradability, and ability to provide a conducive environment for cell growth. This review discusses the use of various biomaterials in MSC-based therapies for endometrial reconstruction and summarizes evidence from preclinical and clinical studies, highlighting the efficacy and safety of these biomaterials. The review also addresses future directions in this field, such as advances in biomaterial engineering, new biomaterials currently under investigation, and personalized medicine approaches. This review emphasizes the significance of biomaterials in MSC-based therapy for endometrial reconstruction and provides practical guidance for developing new materials and treatment protocols for clinical applications.